The spring-mass-model - Andresen, T. (2008)
The spring-mass model (Blickhan and Seyfarth) is a physics-based mathematical tool that treats the human runner as a mass bounding along on two spring-like legs. The total mass of the runner is treated as a single point mass located at the Center of Mass (CM).